Formulasi dan Evaluasi Organoleptik Cookies Tinggi Serat Berbasis Mocaf-Okara pada Diabetes Mellitus Tipe 2 - Nathasa Weisdania Sihite; Anggun Ramadhona; Sriwiyanti Sriwiyanti; Imelda Telisa; Manuntun Rotua (Poltekkes Kemenkes Padang, 2026)
Type 2 Diabetes Mellitus is a chronic hyperglycemic condition that requires appropriate dietary management, including the consumption of high-fiber foods. The utilization of modified cassava flour (mocaf) and okara in cookie production represents a potential alternative snack option for individuals with diabetes mellitus. This research aimed to develop cookies with a higher dietary fiber content compared to conventional cookies, thereby providing a suitable snack alternative for patients with Type 2 Diabetes Mellitus. This study employed a non-factorial Completely Randomized Design (CRD). The cookie formulations consisted of three treatments, namely F1, F2, and F3, with varying proportions of mocaf flour and okara as the primary ingredients. The results demonstrated that the formulations F1 (25:45), F2 (35:35), and F3 (20:50) produced distinct characteristics, with F3 identified as the optimal formulation. The nutritional composition of F3 per 100 g was as follows: energy 561.43 kcal, protein 8.48 g, fat 38.35 g, carbohydrates 45.60 g, and dietary fiber 43.25 g. Conclusion: Increasing the proportion of okara significantly enhances dietary fiber content without notably reducing panelists’ acceptance. It is recommended that future studies incorporate additional sources of complex carbohydrates and conduct glycemic index testing as well as direct intervention trials in Type 2 DM patients to ensure the product meets standards and is supported by stronger scientific evidence.